2020
DOI: 10.1111/are.14551
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of stocking density on the fishPiaractus mesopotamicusfed with red seaweed (Pyropia columbina) and β‐carotene‐supplemented diets

Abstract: This study aimed at investigating the physiological responses of Piaractus mesopotamicus exposed to high stocking density and the potential protective role of supplemented diets. Fish were fed with basal, red seaweed (Pyropia columbina) or β-carotene-supplemented diets for 90 days. Then, fish were distributed at low (1.5 g/L) and high (22 g/L) stocking densities for 15 days. Fish exposed to the high density showed increased hepatosomatic index, haemoglobin content and mean corpuscular haemoglobin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Stress physiology, markers of HSdensity stress and the effects of water quality, feed and water additive to reduce stress were reviewed by Baldwin (2011). Positive effects of feeding fish with some additives such as vitamins (Bacchetta et al, 2020;Naderi et al, 2017), fatty acids (Bahurmiz & Ng, 2007), amino acids such as arginine (Hoseini et al, 2019), tryptophan (Hoseini et al, 2020) and minerals (Adineh et al, 2020;Naderi et al, 2017) to reduce HSdensity stress have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Stress physiology, markers of HSdensity stress and the effects of water quality, feed and water additive to reduce stress were reviewed by Baldwin (2011). Positive effects of feeding fish with some additives such as vitamins (Bacchetta et al, 2020;Naderi et al, 2017), fatty acids (Bahurmiz & Ng, 2007), amino acids such as arginine (Hoseini et al, 2019), tryptophan (Hoseini et al, 2020) and minerals (Adineh et al, 2020;Naderi et al, 2017) to reduce HSdensity stress have been found.…”
Section: Introductionmentioning
confidence: 99%
“…The present results demonstrated that Artemisia is capable with preventing/mitigating the adverse effects of high stocking density on the blood leukocytes. There are no similar study for comparison, but, the results are partially similar to those obtained in small-scaled pacu, Piaractus mesopotamicus, reared under high stocking density and fed a seaweed-supplemented diet (Bacchetta et al, 2020). Humoral soluble immune parameters have been widely using to monitor overall immune status of fish, among them, lysozyme, complement proteins and Ig are the most popular one.…”
Section: Discussionmentioning
confidence: 80%
“…Decreased WBC counts due to stress may compromise the ability of fish to cope with pathogens and other stressors. Decrease in the blood WBC and lymphocyte percentage, and increase in neutrophil percentage have been reported under crowding stress in fish (Bacchetta et al, 2020;Lemos et al, 2018;Zebral et al, 2015). There is no study evaluating the effects of Artemisia on the blood WBC under crowding stress in fish; however, other Artemisia sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stocking density of reared organisms is one of the main factors that determine the productivity of an aquaculture system (Bacchetta et al, 2020). In intensive aquaculture, the stocking density of organisms in water is often increased to obtain higher production and greater economic benefits.…”
Section: Stocking Densitymentioning
confidence: 99%